KELEMAHAN PENERAPAN CLOSED LIST SYSTEM SERTA IMPLIKASINYA DALAM PEMUNGUTAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN - Nabitatus Sa'adah (Faculty of Law, Universitas Diponegoro, 2014)
The Act No. 28 of 2009 of Regional Tax and Retribution is intended to support regional head through tax sector in order to conduct implementation of regional autonomy. There are significant changes in the new law among others are transfer of BPHTB as Districts Tax and implementation of close list system.Implementation of closed list system has several weaknesses such as local government unable to act much if there are provisions of multiple interpretations, which disadvantage the region. Such thing should be demonstrate on regulation related to BPHTB therefore it will create implication of regional disadvantage.